The history of the discourses about passions in Cicero’s Tusculan disputation - Rocha, André Menezes (Cadernos Espinosanos, 2010)
How passion shows itself in Plato’s dialectics? How in the texts of rhetoric? How in the Stoic’s logic? Cicero makes a skeptical examination of many forms of speeches on passions and virtues, in the Tusculan Disputation, searching for grounds for moral philosophy. This examination, which seems to be a history of all ancient texts on the matter, puts in confrontation the great schools of the ancient materialism: Hippocratic medicine, Stoicism, Cyreaism and Epicureanism. The lecture of Cicero’s Tusculan can let us apprehend the different modes of discourse on passions and actions that were developed in Antiquity.